2017
DOI: 10.1177/2050640616650804
|View full text |Cite
|
Sign up to set email alerts
|

The use of enteral access for continuous delivery of levodopa‐carbidopa in patients with advanced Parkinson’s disease

Abstract: While all patients responded well to levodopa-carbidopa regarding neurological outcomes, gastro-intestinal severe adverse events were frequent and related to comorbidities. Endoscopic treatment is the cornerstone for management of PEG-J related events. In conclusion, clinicians and endoscopists, as well as patients, should be fully informed of procedure-related adverse events and patients should be followed in centres experienced in their management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…4,7-14 Viljaharju et al 10 reported that a single case of peritonitis died among 103 patients. Cheron et al 14 reported that one closed duodenal perforation and one intra-abdominal infectious collection were cured with conservative treatment. Ebstein et al 13 reported that five of eight peritonitis cases treated conservatively, three of them surgically, all patients were successfully treated.…”
Section: Discussionmentioning
confidence: 99%
“…4,7-14 Viljaharju et al 10 reported that a single case of peritonitis died among 103 patients. Cheron et al 14 reported that one closed duodenal perforation and one intra-abdominal infectious collection were cured with conservative treatment. Ebstein et al 13 reported that five of eight peritonitis cases treated conservatively, three of them surgically, all patients were successfully treated.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, BBS might be unnoticed until severe symptoms occur or are incidentally identified. It was reported that the frequency of BBS in PEG-J for PD on LCIG treatment was 7.4–17.1%, which was much higher than that of BBS in PEG in general [ 6 , 7 ]. The median interval time between placement of PEG-J and occurrence of BBS was reported to be 25.5 months [ 6 ].Once BBS in PEG-J occurs, simultaneous removal and replacement are ideal to avoid LCIG treatment cessation, but detailed information for its surgical procedure is yet to be introduced.…”
Section: Introductionmentioning
confidence: 99%
“…
Parkinson's disease (PD) is a neurodegenerative disorder characterized by tremor, bradykinesia, rigidity, and postural instability. Degeneration of dopamine-producing neurons results in PD impairments to motor function (Cheron et al, 2017). Levodopa remains the gold standard treatment for PD symptom management; however, the long-term use of oral levodopa is associated with the development of significant complications including motor and nonmotor fluctuations and dyskinesias.
…”
mentioning
confidence: 99%